Microwave-Assisted Copper-Powder-Catalyzed Synthesis of Pyrimidinones from β-Bromo α,β-Unsaturated Carboxylic Acids and Amidines - Ho, Son Long; Cho, Chan Sik (Synlett, 2013)
β-Bromo α,β-unsaturated carboxylic acids were coupled and cyclized with amidine hydrochlorides by microwave irradiation in the presence of catalytic amounts of copper powder and a base to give the corresponding pyrimidinones in high yields.
Keywords: copper; coupling; cyclization; heterocycles; heterogeneous catalysis